Biochemical, Transcriptional, and Bioinformatic Analysis of Lipid Droplets from Seeds of Date Palm (Phoenix dactylifera L.) and Their Use as Potent Sequestration Agents against the Toxic Pollutant, 2,3,7,8-Tetrachlorinated Dibenzo-p-Dioxin - Hanano, Abdulsamie; Almousally, Ibrahem; Shaban, Mouhnad; Rahman, Farzana; Blee, Elizabeth; Murphy, Denis J. (Frontiers in Plant Science, 2016)
Contamination of aquatic environments with dioxins, the most toxic group of persistent organic pollutants (POPs), is a major ecological issue. Dioxins are highly lipophilic and bioaccumulate in fatty tissues of marine organisms used for seafood where they constitute a potential risk for human health. Lipid droplets (LDs) purified from date palm, Phoenix dactylifera, seeds were characterised and their capacity to extract dioxins from aquatic systems was assessed. The bioaffinity of date palm LDs towards 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), the most toxic congener of dioxins was determined. Fractioned LDs were spheroidal with mean diameters of 2.5 m, enclosing an oil-rich core of 392.5 mg.mL-1. Isolated LDs did not aggregate and/or coalesce unless placed in acidic media and were strongly associated with three major groups of polypeptides of relative mass 32-37, 20-24 and 16-18 kDa. These masses correspond to the LD-associated proteins, oleosins, caleosins and steroleosins, respectively. Efficient partitioning of TCDD into LDs occurred with a coefficient of log KLB/w,TCDD = 7.528 ± 0.024; it was optimal at neutral pH and was dependent on the presence of the oil-rich core, but was independent of the presence of LD-associated proteins. Bioinformatic analysis of the date palm genome revealed 9 oleosin-like, 5 caleosin-like, and 5 steroleosin-like sequences, with predicted structures having putative lipid-binding domains that match their LD stabilising roles and use as bio-based encapsulation systems. Transcriptomic analysis of date palm seedlings exposed to TCDD showed strong up-regulation of several caleosin and steroleosin genes, consistent with increased LD formation. The results suggest that the plant LDs could be used in ecological remediation strategies to remove POPs from aquatic environments. Recent reports suggest that several fungal and algal species also use LDs to sequester both external and internally derived hydrophobic toxins, which indicates that our approach could be used as a broader biomimetic strategy for toxin removal.